ANALYSIS OF THE STATE OF CREDIT CONSUMER COOPERATIVES IN THE RUSSIAN FEDERATION - A. R. Simonyan (Вестник университета)
The relevance of the development of the credit consumer cooperatives as a promising segment of the credit market has been substantiated. The state of credit consumer cooperatives has been analyzed in the article. The theoretical foundations of the credit consumer cooperatives have been revealed. The main indicators of the credit consumer cooperatives activity have been adduced and analyzed. Directions of activity of the Central Bank in relation to the credit consumer cooperatives have been reflected. The main problems constraining development of credit consumer cooperatives have been identified. Special attention to the insecurity of property interests of shareholders has been paid. Recommendations for improvement of credit consumer cooperatives activities have been presented. The main conclusion is, that the credit consumer cooperatives have a huge financial and credit potential, but in our country they are not yet sufficiently developed. The mechanisms, adduced in the article, could ensure a steady growth of the credit consumer cooperatives’ activities.